Peran perempuan dalam kebangkitan ekonomi lokal melalui usaha mikro kecil menengah ditinjau dari perspektif ekonomi Islam - Nijla Shifyamal Ulya; Amin Wahyudi (LPMP Imperium, 2022)
Currently, in Indonesia, the activities of MSMEs are increasing rapidly; this is evidenced by the proliferation of micro, small and medium enterprises, which are increasing daily. MSMEs have tremendous potential because they resist the current economic crisis after a prolonged pandemic. This study is also inseparable from the role of women in its implementation. Women have great potential for the progress of MSMEs in Indonesia. This study uses a qualitative method, which refers to a phenomenon by analyzing data sources obtained utilizing interviews, observations, and literature studies from previous studies. Most MSME actors are women with high responsibility, dedication, and honesty. Women can carry out multiple roles to help fulfill the family's economy.